The dictators new clothes: The relationship between e-participation and quality of government in non-democratic regimes - Linde, Jonas; Karlsson, Martin (2013)
It is often assumed that the development of e-participation and e-government initiatives aimed at stimulating citizen participation in the political process and fostering more efficient governmental services harbors a great potential for improved control of corruption and government performance. Thus, it is often argued that e-participation is an efficient instrument for increasing transparency and quality of government in non-democratic and developing countries. However, this article argues that these assumptions should be questioned on theoretical, empirical, and methodological grounds. The results of the empirical time-series cross-section analyses show that positive development in terms of e-participation in non-democratic countries does not lead to corresponding positive effects in terms of control of corruption and quality of government. Rather, in many cases the Internet offers political elites new opportunities in their quest for remaining in power. - Reproduced.
Keywords: E governance